Increasing online consumer satisfaction with logistics service quality: A study in Riau islands province, Indonesia - Sukati, Inda; Tukino; Wangdra, Ronald; Wangdra, Yvonne (International Journal of Management and Sustainability, 2025)
This study’s primary goal was to assess the influence of logistics service quality (LSQ) on online consumer satisfaction (CS) in the Province of Riau Islands, Indonesia. The investigation addresses the various dimensions of LSQ, consisting of the personnel contact quality (PCQ), timeliness delivery quality (TDQ), order discrepancy handling quality (ODHQ), information quality (IQ), and order condition quality (OCQ). Research questionnaires were sent to 500 consumers in the Province of Riau Island, and 344 responses were valid. The investigations employed multiple regression, reliability, and validity tests. All variables–LSQ dimension and CS showed satisfactory reliability and validity. The finding showed that the LSQ dimensions, consisting of PCQ, TDQ, ODHQ, IS, and OCQ, have a significant impact on CS. This study underscores the criticality for logistics companies to enhance their LSQ, as it significantly influences CS and boosts their competitiveness. This research’s approach to exploring logistics services in the e-commerce industry is expected to make significant contributions to logistics service and CS in a more comprehensive study.